Prevalence of non-typhoidal Salmonella enterica in food products in the Middle East and North Africa: A systematic review and meta-analysis. (March 2020) - Al-Rifai, Rami H.; Chaabna, Karima; Denagamage, Thomas; Alali, Walid Q.
Abstract: Food contamination with non-typhoidal Salmonella enterica (NTS) is common in the Middle East and North Africa (MENA) region. A systematic review and meta-analysis were conducted to summarize available data on the overall regional and national-specific NTS prevalence in food products in this region. Published literature of NTS prevalence in food was systematically reviewed and reported following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The overall NTS prevalence was estimated regionally and nationally in MENA with stratification by food commodity, sample size, and period of data collection. Pooled NTS prevalence measures were estimated using a random-effects model. Out of 5, 495 citations screened, 60 research reports published between 1996 and 2018 from 13 countries were eligible. A total of 154 NTS prevalence measures were reported (out of the 60 research reports) representing 24, 023 tested food samples with 1, 324 NTS-positive samples . The pooled NTS prevalence was estimated at 8.8% (95% confidence interval (CI): 7.0–10.8%). The pooled NTS prevalence in food from land animals was 9.0% (95% CI: 6.8–11.4) based on measures from 13 countries. Furthermore, the pooled NTS prevalence in aquatic food products (in four countries) and in plant foods (in six countries) was 22.9% (95% CI: 13.8–33.4%) and 0.4% (95% CI: 0.0–1.9%), respectively. The NTS prevalence was 13.4% (95% CI: 10.1–17.1%) in studies tested <100 food samples compared to 4.1% (95% CI: 2.7–5.8%) in studies tested ≥100 food samples. Country, food commodity, sample size, and period of the data collection were predictors associated with heterogeneity in the NTS prevalence measures. Salmonella Typhimurium (28.0%), S. Enteritidis (23.6%), and S. Kentucky (20.3%) were the most common serotypes in the tested food commodities. The NTS was relatively common in food products consumed in MENA region. Implementation of risk-based food safety systems in the MENA region may reduce the burden of NTS in food, and therefore improve public health. Highlights: Salmonella is a common cause of foodborne disease in humans worldwide. This review summarized burden of non-typhoidal Salmonella in food in MENA countries. This pathogen was common, mainly in aquatic and animal food products in MENA. Findings emphasize the need for improved research and inform food safety systems.